THE ISLAMIC ASSOCIATION OF CHINA DAN KEPENTINGAN ETNIS MINORITAS MUSLIM DI REPUBLIK RAKYAT CINA - , NADYA PRIMA HAFNI ARIFIN, Dr. Nur Rachmat Yuliantoro, MA (IR) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Republic of China is a nation with various ethnicity, led by The Communist Party of China. Muslims as an ethnic minority has developed quite well in this country, alongside a number of needs that has to be accommodated. This thesis is going to elaborate the means and strategies of the Islamic Association of China (IAC, Zhingguo Yisilanjiao Xiehui) to accommodate muslims as an ethnic minority in The Republic of China. The fulfillment of their rights is in accordance to the improvement of education and the society's adjustment of living ability, economic adaptability, and their satisfaction rate related to The Communist Party of China's regime of power. Furthermore, this thesis will also elaborate The Communist Party of China's response due to the establishmeent of IAC, and The Communist Party of China's intention, which is achieving national integration through IAC's activities. Although, IAC's activities will of course be affected by The Communist Party of China's regulations that tends to lean towards prioritizing China's collective values in the society's structural organization. In this case, IAC is privileged with a rational choice in determining its objective as well as its activities, thus in the practice IAC would thrive through the challenges and still achieve islamic values without contradicting The Communist Party of China's national integration and patriotic values.